Pathogenesis of cerebral malaria: new diagnostic tools, biomarkers, and therapeutic approaches - Sahu, Praveen K.; Satpathi, Sanghamitra; Behera, Prativa K.; Mishra, Saroj K.; Mohanty, Sanjib; Wassmer, Samuel Crocodile (Frontiers in Cellular and Infection Microbiology, 2015)
Cerebral malaria is a severe neuropathological complication of Plasmodium falciparum infection. It results in high mortality and post-recovery neuro-cognitive disorders in children, even after appropriate treatment with effective anti-parasitic drugs. While the complete landscape of the pathogenesis of cerebral malaria still remains to be elucidated, numerous innovative approaches have been developed in the recent years in order to improve the early detection of this neurological syndrome, and subsequently, the clinical care of affected patients. In this review, we briefly summarize the current understanding of cerebral malaria pathogenesis, compile the array of new biomarkers and tools available for diagnosis and research and describe the emerging therapeutic approaches to tackle effectively cerebral malaria.